Anticoagulant Activity of Some Medical Plant Extracts: Allium sativum, Allium Cepa, and Zingiber Officinale - Ali Alkafhage, Fatema (Kerbala Journal of Nursing and Health Sciences., 2025)
The venous and arterial thromboembolic disorders are still be the major cause of morbidity , mortality worldwide.. Allium sativum(Garlic), Zingiber officinale and Allium Cepa are a largely universal staple herb popular throughout history as both food and medicine and it has been consumed for prevention of cardiovascular disorders. In vitro anticoagulant effects of an aqueous extract (5%) of Allium sativum(Garlic), Zingiber officinale and Allium Cepa in different volumes were examined on the blood samples of normal individuals by measuring prothrombin time (PT) The Allium cepa extract It was found that the 2 ml concentration was the most effective and active in preventing the clotting process, as the clotting time was more than an hour compared to the rest of the concentrations and the control sample (which did not contain the extract)., when the Allium sativum extract showed a (1.5,2)ml concentration was the most effective and active in preventing the clotting process, as the clotting time was more than an 24hour compared to the rest of the concentrations and the control tube and the zingiber pfficinale extract showed a significant difference between the concentrations the most effective concentration was 1.5 ml, and by monitoring the clotting time, the clotting time was more than an hour compared to the control sample. Through their bioactive compounds research into their mechanisms of action and clinical applications is necessary to substantiate their use in modern medicine.